Reading numbers system for portuguese language - Teixeira, João Paulo (2018)
The paper presents an algorithm for read common numbers until one million in Portuguese language. The record and cutting process of the digit speech sounds deserved a special attention to improve the speech sound output. A special attention is required for the correct inclusion of the particle ‘e’ (and) to provide better naturalness of the read numbers. The system has the ability of simulate the human biologic speech sound production in the task of reading numbers. The system is based in the concatenation of carefully recorded edited and selected speech segments corresponding to the digits. The naturalness of the system was improved with the use of speech files of read digits in different positions (beginning, middle and end) and using digits concatenated with the particle ‘e’ before, after and before and after the digit.